Analisis Pendampingan Orang Tua dalam Pembelajaran Daring Pada Siswa Kelas 1 SD Negeri Paremono 4 Mungkid - Widyawati, Rita (Prosiding University Research Colloquium, 2021)
The study was intended to analyze parental assistance in online learning during the Covid-19 period of 1st Graders of SD Negeri 4 Mungkid. The study is a qualitative descriptive approach with case studies. The data source usedwas the parents as the first responders, the teachers, and students grade 1st at SD NegeriParemono 4 Mungkid. The method of data collection in this study is that of interviews,observations, archivist documents, and questionnaries. The validity test of data used istechnical triangulation (interviews, observations, archivist document, and questionnaries)and source triangulation (parents, teachers, and students). Data analysis involves the fourcomponents of data collection, data reduction, data presentation, and deduction drawing.The research result obtained are an analysis of parental assistance in online learning. 90%of parents think that online learning is less effective to implement because it is difficult toallocate time to accompany and work. Even so, parents still try to arrange time toaccompanu their children during learning and provide learning support facilities.Although in practice there are obstacles encountered by parents and children, parentsalways try to be able to overcome obstacles by collaborating between parents and teachers